Identification of Protective CD8 T Cell Responses in a Mouse Model of Zika Virus Infection - Hassert, Mariah; Harris, Madison G.; Brien, James D.; Pinto, Amelia K. (Frontiers in Immunology, 2019)
Many flaviviruses including dengue (DENV), and Zika (ZIKV) have attracted significant attention in the past few years. As many flaviviruses are spread by arthropods, most of the world’s population is at risk of encountering a flavivirus, and infection with these viruses has created a significant disease burden worldwide. Vaccination against flaviviruses is thought to be one of the most promising avenues for reducing the disease burden associated with these viruses. The optimism surrounding a vaccine approach is supported by the highly successful vaccines for yellow fever and Japanese Encephalitis. Central to the development of new successful vaccines is the understanding of the correlates of protection that will be necessary to engineer into new vaccines. To aid in this endeavor we have directed our efforts to identify correlates of protection that will reduce the disease burden associated with ZIKV and DENV. Within this study we have identified a novel murine ZIKV specific CD8+ T cell epitope, and shown that the ZIKV epitope specific CD8+ T cell response has a distinct immunodominance hierarchy present during acute infection and is detectible as part of the memory T cell responses. Our studies confirm that ZIKV-specific CD8+ T cells are an important correlate of protect for ZIKV and demonstrate that both naïve and ZIKV immune CD8+ T cells are sufficient for protection against a lethal ZIKV infection. Overall this study adds to the body of literature demonstrating a role for CD8+ T cells in controlling flavivirus infection.